2008
DOI: 10.1158/0008-5472.can-08-1395
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Integrin α1β1 Ameliorates Kras-Induced Lung Cancer

Abstract: The collagen IV binding receptor integrin A1B1 has been shown to regulate lung cancer due to its proangiogenic properties; however, it is unclear whether this receptor also plays a direct role in promoting primary lung tumors. To investigate this possibility, integrin A1-null mice were crossed with KrasLA2 mice that carry an oncogenic mutation of the Kras gene (G12D) and develop spontaneous primary tumors with features of non-small cell lung cancer. We provide evidence that KrasLA2/A1-null mice have a decrease… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 47 publications
1
31
1
Order By: Relevance
“…Reduced experimental tumorigenesis in lung cancer models (Chen et al, 2005;Macias-Perez et al, 2008).…”
Section: Inflammation In Knockout Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced experimental tumorigenesis in lung cancer models (Chen et al, 2005;Macias-Perez et al, 2008).…”
Section: Inflammation In Knockout Modelsmentioning
confidence: 99%
“…2). Furthermore, the absence of α1 has been found to ameliorate or reduce tumor growth and metastasis in a number of lung cancer models (Chen et al, 2005;Macias-Perez et al, 2008). Careful investigation of the role of α1 in the colon has revealed that it is expressed on both epithelial cells and submucosal myofibroblasts (Boudjadi et al, , 2015.…”
Section: α10β1mentioning
confidence: 99%
“…ITGA1, part of the integrin signaling and virus entry via endocytic pathways as identified by IPA, is involved in cell proliferation (Macias‐Perez et al ., 2008) and invasion (Yang et al ., 2015), as well as inflammation (Becker et al ., 2013) and fibrosis (Ramos et al ., 2012), which have all been previously linked to APE1 (Aamann et al ., 2016; Shah et al ., 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Note In mouse models, the α1β1 integrin mediates cell invasion through the regulation of stromelysin-1 expression (Lochter et al, 1999) and, together with the Kras oncogenic factor, potentiates tumour growth and cell motility (Macias-Perez et al, 2008).…”
Section: Lung Cancermentioning
confidence: 99%